The Effectiveness of Using Kahoot in Supporting Learning at Elementary Schools - Kiki Oktaviani; Fatma Azzaahra (JEICI - Journal of Education and Islamic Contemporary Issue, 2025)
In the Era of Industrial Revolution 4.0 which is sweeping all life the world of education must be able to adapt to technological developments, For an educator, mastery and knowledge of technology (technological knowledge) is a competency that must be mastered in order to support improving the learning process. Kahoot! is one of the learning media that can support the learning process to be more effective. The research method chosen was the Literature Review method. Collection data was carried out by documenting and reviewing several articles regarding effectiveness of using Kahoot! in the field of education, especially schools Base. This research uses 10 articles published in the period 2019-2021. This article was obtained from the Google Scholar database. Based on this research, it can be concluded that the use of applications Kahoot! very